2021
DOI: 10.1093/nar/gkab1226
|View full text |Cite
|
Sign up to set email alerts
|

Highly conserved s2m element of SARS-CoV-2 dimerizes via a kissing complex and interacts with host miRNA-1307-3p

Abstract: The ongoing COVID-19 pandemic highlights the necessity for a more fundamental understanding of the coronavirus life cycle. The causative agent of the disease, SARS-CoV-2, is being studied extensively from a structural standpoint in order to gain insight into key molecular mechanisms required for its survival. Contained within the untranslated regions of the SARS-CoV-2 genome are various conserved stem-loop elements that are believed to function in RNA replication, viral protein translation, and discontinuous t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
101
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(112 citation statements)
references
References 99 publications
11
101
0
Order By: Relevance
“…Any host pathway affected by the s2m is likely to be highly conserved since the s2m has been identified in viruses that are predicted to infect mammals, birds, and insects 6 . It is also possible that the s2m is a key element for viral RNA-RNA interactions during the viral lifecycle, as suggested by others 33,34 .…”
Section: Discussionmentioning
confidence: 88%
“…Any host pathway affected by the s2m is likely to be highly conserved since the s2m has been identified in viruses that are predicted to infect mammals, birds, and insects 6 . It is also possible that the s2m is a key element for viral RNA-RNA interactions during the viral lifecycle, as suggested by others 33,34 .…”
Section: Discussionmentioning
confidence: 88%
“…7,8 Specifically, conserved elements within coronavirus genomes are enticing targets for antiviral intervention due to an implied biological function and phylogenetic stability unlike other targets that vary due to constant mutation and contribute to immune escape. [9][10][11] However, complete atomistic structures of conserved sequences from experimental data have yet to be reported to guide the design and development of SARS-CoV-2 antiviral therapies.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19][20][21] Although there is abundant speculation on the function of s2m in the field, 10,13,[18][19][20][21][22][23] we have reported that s2m contains a palindromic sequence in its terminal loop (GUAC, nt 20-23, Figure 1), a striking similarity to the conserved dimerization initiation site (DIS) in the human immunodeficiency virus (HIV) and X55 region in the hepatitis C virus (HCV). 11,24,25 During kissing complex formation between monomer RNA hairpin loops, unpaired terminal loop nucleotides form intermolecular base pairs facilitated through palindromic sequences. 26 Functionally, in these viral systems, these hairpins form kissing complexes that are converted to extended duplexes by the viral capsid protein, being involved in the genome dimerization.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations